2021
DOI: 10.1002/adsc.202100571
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of SpirothiazolonesviaCooperative Catalysis

Abstract: Cooperative amino‐ and palladium catalysis utilizing heterocyclic systems containing strongly coordinating and adsorptive sulfur atom remains an underdeveloped area. Herein, we describe an enantioselective cyclization of enals with thiazole derivatives catalyzed with the combination of achiral Pd(0) complexes and chiral secondary amines. Chiral spirocyclic thiazolones were produced in yields ranging from 41% to 98% with stereoselectivities (from 5:1 to 12:1 dr, and 95–99% ee). Moreover, the developed strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…With this regard, we have reported the first enantioselective synthesis of such compounds from tetrahydro‐1 H ‐oxepine thiazole derivatives 21 and enals 2 under synergistic catalysis of Hayashi Jørgensen chiral secondary amine/Pd(0) system (Scheme 11). [65] Following up on our previous successful ring contraction strategy applied on tetrahydro‐1 H ‐oxepine pyrazoles, we anticipated similar reactivity of the seven‐membered ring thiazole derivatives in the presence of a palladium catalyst. Gratifyingly, any disruptive effect of sulfur on the palladium complex was not observed, and the reaction proceeded smoothly with enals 2 .…”
Section: Covalent Organocatalysis: Synergistic Approachesmentioning
confidence: 81%
See 1 more Smart Citation
“…With this regard, we have reported the first enantioselective synthesis of such compounds from tetrahydro‐1 H ‐oxepine thiazole derivatives 21 and enals 2 under synergistic catalysis of Hayashi Jørgensen chiral secondary amine/Pd(0) system (Scheme 11). [65] Following up on our previous successful ring contraction strategy applied on tetrahydro‐1 H ‐oxepine pyrazoles, we anticipated similar reactivity of the seven‐membered ring thiazole derivatives in the presence of a palladium catalyst. Gratifyingly, any disruptive effect of sulfur on the palladium complex was not observed, and the reaction proceeded smoothly with enals 2 .…”
Section: Covalent Organocatalysis: Synergistic Approachesmentioning
confidence: 81%
“…[62][63][64] With this regard, we have reported the first enantioselective synthesis of such compounds from tetrahydro-1H-oxepine thiazole derivatives 21 and enals 2 under synergistic catalysis of Hayashi Jørgensen chiral secondary amine/Pd(0) system (Scheme 11). [65] Following up on our previous successful ring contraction strategy applied on tetrahydro-1H-oxepine pyrazoles, we anticipated similar reactivity of the seven-membered…”
Section: Aminocatalysis and Transition-metal Catalysismentioning
confidence: 86%
“…It was found that switching the solvent from ethyl acetate to acetonitrile enhanced the diastereocontrol, and that the Pd catalyst loading could be reduced to 2% without reduction in reaction efficiency or enantioselectivity. 67 …”
Section: Ionic Reactivitymentioning
confidence: 99%
“…It was found that switching the solvent from ethyl acetate to acetonitrile enhanced the diastereocontrol, and that the Pd catalyst loading could be reduced to 2% without reduction in reaction efficiency or enantioselectivity. 67 Rios and Veselý then went on to demonstrate that [5,5]-spirobicyclic pyrazolones could also be synthesised in an intermolecular Michael/Conia-ene cascade using synergistic Pd and iminium ion catalysis, with an alkyne-containing monocyclic pyrazolone starting material acting as a ring-opened analogue of the [5,7]-bicycle in their original approach. 68 This transformation only required low loadings of both catalysts to proceed whilst still giving the spiropyrazolone scaffolds 39-42 in impressive ee and with acceptable diastereocontrol.…”
Section: Reviewmentioning
confidence: 99%
“…33 Recently, we successfully applied this concept in the stereoselective annulation reaction of 4-nitroisoxazole-derived alkenes. 34 Drawing on our longstanding interest in developing organocatalytic strategies for the construction of spirocyclic compounds, [35][36][37][38][39][40][41] we aimed for a novel stereocontrolled, NHCcatalyzed spiroannulation of electron-deficient alkenes derived from benzofuran-2-one and in situ generated azolium dienolate intermediate (Fig. 1C).…”
Section: Introductionmentioning
confidence: 99%